Depositional Controls of the Layered Deposits of Arabia Terra, Mars: Hints From Basin Geometries and Stratigraphic Trends. Issue 11 (6th November 2021) - Schmidt, G.; Pondrelli, M.; Salese, F.; Rossi, A.P.; Le Deit, L.; Fueten, F.; Salvini, F.
Abstract: An extensive distribution of water‐altered equatorial layered deposits (ELDs) characterizes the densely cratered terrain of Arabia Terra (AT), Mars. The majority of these deposits reside within craters and are easily identified by laterally continuous layering. The processes that led to their formation have been widely investigated, but remain unresolved. Furthermore, their precise spatial distribution as a whole, as well as their relationship to one another individually, has yet to be fully appreciated. This work examines 1, 013 craters and emphasizes 45 that were observed to contain ELDs within the eastern half of AT. We present the statistical relationships between crater characteristics (e.g., location, diameter, depth), as well as evidence supporting a southeast‐northwest facies change. The 30–2, 000‐m range of measured deposit thicknesses, accompanied with individual layer thicknesses, correlate with crater elevation either due to water level differences within craters, or a proximal‐distal relationship to the source. Air fall or fluid expulsion appear to stand out among all the prevailing depositional hypotheses, however the volume required to fill these craters in an ash fall scenario is in opposition with the locations of known volcanic provinces and the volume of ash that volcanic eruptions produce. This new evidence of a regional facies change provides a unique opportunity to better understand past climate and sedimentary processes on Mars, as well as the putative groundwater level in ancient AT. Ultimately, our results do not agree well with a unified depositional method for these deposits and the possibility of mixed origins should be taken seriously. Plain Language Summary: Layer thicknesses of equatorial layered deposits (ELDs) within craters in western Arabia Terra (AT) show a regional NW‐SE thickening, correlating with both elevation and latitude. The trend does not correlate with locations of established volcanic provinces or proposed locations of nearby calderas. Additionally, the volume necessary to completely fill craters may be problematic in an ash fall scenario. The discrepancy of ELD size between craters is problematic and requires specialized erosional intensities unique to each crater. Fluctuating water level might create a proximal‐distal effect either from the putative ocean to the northwest which hinders thicker ELD formation, or fluid expulsion focused at Meridiani Planum which aids thicker ELD formation. Thinning and thickening sequences in individual craters suggests repeated changes from low to high energy environments. Low to moderate layer attitudes are indicative of compaction or draping during deposition over pre‐existing topography, whereas steeply dipping layers suggests post‐depositional deformation in specific craters. This implies post‐depositional histories are often unique to individual craters. Observations demonstrate that determining the depositional method requires a regional overview to establish the controls that create these unique characteristics. Thus, a unifying depositional theory does not fit all characteristics of ELDs in AT and multiple or mixed origins should be considered. Key Points: Geological evidence supporting a SE‐NW facies change within intracrater layered deposits in western Arabia Terra Measurements of deposit thickness and individual layer thickness decrease with elevation and latitude The volume required to fill these craters in an air fall scenario is in opposition with the locations of known volcanic provinces and the volume of ash volcanic eruptions produce